1983
DOI: 10.1289/ehp.835311
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of dietary exposure to amosite and chrysotile asbestos in Syrian golden hamsters.

Abstract: Bioassays of amosite, short-range (SR), intermediate-range (IR) or intermediate-range chrysotile asbestos in combination with the intestinal carcinogen 1,2-dimethylhydrazine dihydrochloride (DMH) were conducted with male and female Syrian golden hamsters. Amosite and both forms of chrysotile asbestos were administered at a concentration of 1% in pelieted diet for the entire lifetime of the hamsters starting with mothers of the test animals. Group sizes varied from 125-254. There was no adverse effect on body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The best available technology for determining asbestos content in water is described in a 1983 EPA project report (20 (29,30). All of these studies used animals reared from dams exposed to the asbestos fibers.…”
Section: Recommended Sampling Methods For Detecting Asbestos Fibers Inmentioning
confidence: 99%
“…The best available technology for determining asbestos content in water is described in a 1983 EPA project report (20 (29,30). All of these studies used animals reared from dams exposed to the asbestos fibers.…”
Section: Recommended Sampling Methods For Detecting Asbestos Fibers Inmentioning
confidence: 99%
“…For more details about the full method and the rapid method, the reader is referred to the EPA report. Toxicology To date, 11 toxicologic studies on asbestos ingestion have been conducted (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Eight of these studies have been reviewed by Condie (32), who concluded that the studies do not provide substantive support for an association between ingestion of asbestos fibers and the induction of cancer.…”
Section: Recommended Sampling Methods For Detecting Asbestos Fibers Inmentioning
confidence: 99%
“…Two recent reports from the National Toxicology Program (NTP) have shown no carcinogenic response after lifetime exposure of Syrian golden hamsters to 1% amosite or chrysotile asbestos in the diet and in F344 rats which were fed 1% amosite or tremolite in their diet during a lifetime study (29,30). All of these studies used animals reared from dams exposed to the asbestos fibers.…”
Section: Recommended Sampling Methods For Detecting Asbestos Fibers Inmentioning
confidence: 99%
“…In vivo intestinal permeability studies with long term ingested chrysotile in the drinking water (0.5 g/L), absorptional ability of non-metabolizable sugars was decreased in GIT [74]. But, McConnell group showed that toxic or neoplastic lesions are not observed in gastrointestinal tract and mesothelium in Fischer 344 rat and in Syrian golden hamsters given the diet with amosite (at a concentration of 1% of pelleted diet) for their lifetime even though increasing C-cell carcinomas of the thyroid and monocyte significantly [75,76]. …”
Section: Mechanism Study Of Gi Cancer By Asbestosmentioning
confidence: 99%